2009
DOI: 10.1007/s11250-009-9458-9
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of some tropical grasses used by traditional small farms in the highlands of Burundi

Abstract: The objective was to estimate--according to the French feeding system--the nutritive value of three tropical grasses (Eragrostis olivacea, Setaria sphacelata and Tripsacum laxum) used in traditional small farms of Burundi. Dry matter (DM) yield was monitored on anti-erosive hedges or on small fields in 60 small farms for eight consecutive years. DM intake and digestibility values were measured on seven steers or seven male sheep. Degradability values were determined on three sheep. S. sphacelata exhibited high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In orchard grass, 72.4 and 43.8% DM respectively for NDF and ADF were recorded (Bourquin et al, 1994). The study of three tropical grasses commonly used in traditional small farms of Burundi showed 85.1, 69.5 and 70.5% DM for NDF against 45.4, 37.4 and 37.1% DM for ADF respectively for Eragrostis olivacea, Setaria sphacelata and Tripsacum laxum (Nivyobizi et al, 2010). In fact, maturity was mainly considered to be the key factor affecting forage quality, and many reports have focused on season and growth stage of forage since some factors affect its feeding value (Minson, 1990;Borreani et al, 1998).…”
Section: Chemical Compositions Of E Pyramidalismentioning
confidence: 99%
“…In orchard grass, 72.4 and 43.8% DM respectively for NDF and ADF were recorded (Bourquin et al, 1994). The study of three tropical grasses commonly used in traditional small farms of Burundi showed 85.1, 69.5 and 70.5% DM for NDF against 45.4, 37.4 and 37.1% DM for ADF respectively for Eragrostis olivacea, Setaria sphacelata and Tripsacum laxum (Nivyobizi et al, 2010). In fact, maturity was mainly considered to be the key factor affecting forage quality, and many reports have focused on season and growth stage of forage since some factors affect its feeding value (Minson, 1990;Borreani et al, 1998).…”
Section: Chemical Compositions Of E Pyramidalismentioning
confidence: 99%